Dietary magnesium intake and risk of hypertension among adult outpatients - Umi Hasanah; Effatul Afifah; Esti Nurwanti (Alma Ata University Press, 2017)
ABSTRACTBackground : Hypertension still has been a great health problem in indonesia. In Indonesia, the prevalence of hypertension in 2013 was as many as 28.5 %, and in The Yogyakarta special was as many as 25,7 %. Several factors that can affect hypertension, some unavoidable as aging and sex, but some can as lifestyle very closely related to nutrition as deficiency intake calcium and magnesium[LAL1] . Calcium may affect blood pressure because it inhibits the effects of the intake of salt naci high on blood pressure. And if less magnesium it can increase levels of sodium intracellular and sent down the potassium intracellular. [LAL2] Objectives : To know the relationship between calcium and magnesium intake with the genesis hypertension in outpatients at RSUD Panembahan Senopati Bantul Yogyakarta.Methods : The research was observational with case-control[LAL3] design. Research was carried out in February 2016 and population research was outpatients RSUD Panembahan Senopati Bantul Yogyakarta. Sample case was outpatients the age of 30-60 years with the diagnosis hypertension. Control is outpatients with the age of 30-60 years who do not hypertension. The sample of the 45 patients with comparison cases control 1: 1, so the total sample was 90 patients with 45 patients hypertension and 45 a patient was not hypertension .Sampling method was by purposive sampling. Variable dependent was hypertension and independent variable was calcium and magnesium intake.[LAL4] An instrument was form food frequency questionary (FFQ) form that was taken by means of interview. Data analysis using analysis univariate ( descriptive with the spss version 19 and bivariat (test chi-square).Result : Bivariat analysis showed that calcium intake (p = 0.827; or = 0.909; el 95 % = 0.385 – 2.143) no significant relationship with the occurrence of hypertension .While intake of magnesium (p = 0.035; or = 2.471; el 95%= 1.058 - 5.768) had significant relationship with the occurrence of hypertension.Conclusion : A significant relation was between magnesium and the genesis hypertension. Was proven but intake calcium did not prove the relationship with the genesis hypertension[LAL5] . KEYWORDS : hypertension, calcium and magnesium intake